Private sector led multi-stakeholder platforms positively influence certified seed supply in Malawi - Gondwe, Wanangwa; Phiri, Alexander; Birachi, Eliud; Magreta, Ruth; Larochelle, Catherine; Machira, Kennedy; Mutua, Mercy; Rubyogo, Jean Claude; Nkhata, Wilson (Elsevier, 2024)
Common bean yields in Malawi remain low, primarily due to the use of low-yielding, recycled local seeds by most smallholder farmers. The low uptake of certified bean seed is attributed to limited incentives from the private sector. This study hypothesizes that the sustainable adoption of market-preferred varieties can be achieved by synchronizing and linking seed production to the grain market through committed value chain actors in a private sector-led multi-stakeholder platform. This paper examines the role of private sector-led multi-stakeholder platforms in the supply of certified common bean seed in Malawi. The research draws on both qualitative and quantitative primary data collected through a semi-structured questionnaire and interviews with key informants. Data were analyzed using an Ordinary Least Squares (OLS) regression model. The results indicate that several variables representing membership in multi-stakeholder platforms (MSPs) significantly affect the supply of certified common bean seed. Participation in MSPs, contractual arrangements, market structure, extension services, and seed demonstrations positively influenced seed supply. The findings underscore the need for a well-coordinated multi-stakeholder platform to enhance the supply of certified common bean seed, supported by effective policies and incentives from policymakers.